Stability Analysis of Gabion wall with Tieback in Seismic Regions - Asadpour, Hamid; Akhlaghi, Tohid (Civil Engineering Journal, 2017)
One of the most important issues in the construction of highways, mountain and urban roads is known as slope stabilization. If the necessary actions for protection are not considered, it could lead to problems and events such as landslides, settlements and even destruction of roads. There are many methods for stabilizing slopes such as Gabion walls and Tiebacks. This study can be used as the beginning of a new synthetic method where the Gabion wall is combined with Tiebacks. Gabion walls and tiebacks can be known as the most flexible methods of slope stabilization methods, because of this reason, if they can be combined with each other, it should show very good results in front of dynamic and even static forces. This combination is the novel point of this research. In this study at first, the gabion wall will be analysed in different loading conditions, and then to deal with earthquake dynamic forces the tiebacks will be used to increase the gabion walls stability.The software that is used in this study is GEO5 software, nowadays this software can be introduced as one of the best slope stability analysis softwares. The results of this study showed that the designed gabion wall could be stable in dense silty gravel soil (GM) in 8.5-meter slope, and with magnitude of 0.25 horizontal coefficient of Manjil earthquake, but in the same geometry and material condition and impact of 0.4 magnitude horizontal coefficient of Bam earthquake it couldnt be stable alone. In this condition four rows of 18 meter tiebacks could stable the gabion wall very well. In this model, under loading condition 3 (with horizontal and vertical pseudo-static coefficient of Bam earthquake) that had the most vertical pseudo-static coefficient, the 23-meter tieback anchors with 12-degree inclination respect to horizontal could stable the considered gabion wall. This result could show that, the combination of gabion walls with tieback anchors gives a satisfactory result and it is an efficient and helpful method for stability of slopes in front of earthquake and dynamic forces.